ANALYSIS OF CREPER MACHINE UTILIZATION IN CRUMB RUBBER PRODUCTION BASED ON BLANKET THICKNESS DISTRIBUTION AT PT. PANTJA SURYA - Purba, Reza Hazly Al’Udlu; Siregar, Rohimah Nurul Huda; Alysha Tasya Aulia; Situmorang, Tiur Nauli; Siregar, Nisa Zahra Gustiani; Nasution, Budiman; Situmorang, Howard; Nasution, Habibi Azka (EINSTEIN (e-Journal), 2026)
Creper machines are vital in crumb rubber processing for reducing material thickness and ensuring blanket quality. This study provides a quantitative physical analysis of five creper machines at PT. Pantja Surya, focusing on how pressure force and maintenance schedules correlate with blanket thickness distribution. Primary data were collected through field observations and technical equipment specifications, which were subsequently analyzed using the Python programming language to calculate mechanical parameters, including the reduction ratio, roll-material contact length (Lp), and estimated compressive force (F). The results indicated that the maximum mechanical load was concentrated on Creper 1, with an estimated compressive force of 867.85 kN, correlating with the maximum contact length of 0.177 m. An anomaly was observed in Creper 3, which functions as a transition stage without thickness reduction to stabilize the material's viscoelasticity. The distribution of compressive force gradually decreases in Crepers 4 and 5 (382.57 kN and 352.28 kN, respectively), consistent with a more controlled reduction process. This analysis demonstrates that units subjected to higher compressive forces require shorter maintenance intervals (120 hours) compared to units with lower loads (160 hours). Consequently, these findings establish a framework for implementing load-based predictive maintenance to enhance operational efficiency in the industry.